In vitro Activity of Sparfloxacin and Its Combination with Efflux Pump Blockers Against Methicillin-Resistant Staphylococcus aureus and Escherichia coli - Rahima Tahir; Neha Farid; Khansa Syed; Misbah Mohammad Hanif; Asma Bashir; Kashif Ali (Pakistan Journal of Medicine and Dentistry)
Background: Multi-drug resistance has emerged as a significant global health challenge that has resulted in the occurrence of numerous diseases. This paper highlighted the potential of Sparfloxacin as a solution to antimicrobial resistance when used alone or in combination with efflux pump blockers. Sparfloxacin is a fluoroquinolone antibiotic that inhibits the bacterial DNA gyrase, thereby preventing DNA replication.  The purpose of this study was to determine the efficacy of Sparfloxacin against MRSA and E. coli, and whether it could be used either solely or in combination with the efflux pump blockers to overcome multidrug resistance.